Potential for urban agriculture to support accessible and impactful undergraduate biology education. Issue 3 (14th March 2022) - Kay, Adam D.; Chapman, Eric J.; Cheruiyot, Jelagat D.; Lowery, Sue; Singer, Susan R.; Small, Gaston; Stone, Anne M.; Warthen, Ray; Westbroek, Wendy
Abstract: Active learning in STEM education is essential for engaging the diverse pool of scholars needed to address pressing environmental and social challenges. However, active learning formats are difficult to scale and their incorporation into STEM teaching at U.S. universities varies widely. Here, we argue that urban agriculture as a theme can significantly increase active learning in undergraduate biology education by facilitating outdoor fieldwork and community‐engaged education. We begin by reviewing benefits of field courses and community engagement activities for undergraduate biology and discuss constraints to their broader implementation. We then describe how urban agriculture can connect biology concepts to pressing global changes, provide field research opportunities, and connect students to communities. Next, we assess the extent to which urban agriculture and related themes have already been incorporated into biology‐related programs in the United States using a review of major programs, reports on how campus gardens are used, and case studies from five higher education institutions (HEIs) engaging with this issue. We found that while field experiences are fairly common in major biology programs, community engagement opportunities are rare, and urban agriculture is almost nonexistent in course descriptions. We also found that many U.S. HEIs have campus gardens, but evidence suggests that they are rarely used in biology courses. Finally, case studies of five HEIs highlight innovative programming but also significant opportunities for further implementation. Together, our results suggest that urban agriculture is rarely incorporated into undergraduate biology in the United States, but there are significant prospects for doing so. We end with recommendations for integrating urban agriculture into undergraduate biology, including the development of campus gardens, research programs, community engagement partnerships, and collaborative networks. If done with care, this integration could help students make community contributions within required coursework, and help instructors feel a greater sense of accomplishment in an era of uncertainty. Abstract : We argue that urban agriculture is well suited as a theme for undergraduate biology education because it will facilitate the incorporation of outdoor fieldwork and community‐engaged education into the curriculum. In the manuscript, we review potential educational benefits of field courses and community engagement activities for undergraduate biology and discuss constraints to their broader implementation. We also assess the extent to which urban agriculture and related themes have already been incorporated into Biology‐related programs and make recommendations for incorporating urban agriculture into biology curricula.